Suppression of stored-beam oscillation and observation of flux improvement during top-up injection - Y-G. Son; J.-Y. Kim; C. Mitsuda; K. Kobayashi; J. Ko; T-Y. Lee; J-Y. Choi; D-E. Kim; H-S. Seo; H-S. Han; K-S. Park; C-D. Park; et al. (Physical Review Accelerators and Beams, 2017)
This paper describes a start-to-end study of the suppression of stored-beam oscillation during top-up injection at the Pohang Light Source (PLS-II) beam line. The fast counterkicker implemented in PLS-II suppresses stored-beam oscillations in the vertical plane. During top-up injection in the magnetic spectroscopy beam line of PLS-II, flux improvement due to the suppression of stored-beam oscillation was clearly observed.